2020
DOI: 10.3727/154427219x15741004672666
|View full text |Cite
|
Sign up to set email alerts
|

Examining Tour Services, Satisfaction, and Loyalty Of International Tourists in Cape Coast, Ghana

Abstract: Utilizing transaction-specific customer satisfaction theory within tourism marketing, this research investigates how tour services elicit international tourists' satisfaction and contribute to tourists' loyalty to a destination. The research was conducted using 356 international tourists visiting destination sites in Cape Coast who answered questions regarding tour services: accommodation, food services, tour guide performance, souvenir shopping, and community interaction. Structural equation modeling was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Increased tourist satisfaction may also boost loyalty to a destination. Tourists with greater satisfaction are more inclined to revisit and recommend destinations to others (Alexandris et al, 2006;Chi and Qu, 2008;Preko et al, 2020). Destination management organizations should therefore prioritize managing the destination's image and the quality of the services provided, as these factors can affect tourist satisfaction and intention to revisit (Chi and Qu, 2008).…”
Section: Relationships Between Tourist Satisfaction and Tourist Behav...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased tourist satisfaction may also boost loyalty to a destination. Tourists with greater satisfaction are more inclined to revisit and recommend destinations to others (Alexandris et al, 2006;Chi and Qu, 2008;Preko et al, 2020). Destination management organizations should therefore prioritize managing the destination's image and the quality of the services provided, as these factors can affect tourist satisfaction and intention to revisit (Chi and Qu, 2008).…”
Section: Relationships Between Tourist Satisfaction and Tourist Behav...mentioning
confidence: 99%
“…Fernandes and Cruz (2016) argued that wineries should create a pleasant experience to enhance tourists' satisfaction and thus their behavioral intentions. Preko et al (2020) demonstrated that effective tourism services and tourist satisfaction can contribute to tourist loyalty and revisit intention. Thus, we propose the following hypotheses:…”
Section: Relationships Between Tourist Satisfaction and Tourist Behav...mentioning
confidence: 99%
“…In the words of Wei et al (2021a, b), memorable experiences drive behavioral intentions; that includes the intention and willingness to pay a premium price for tour services. Tourists are also driven to visit locations they believe are worthy (Preko et al , 2020a, b), which is impacted by destination trust and is a key driver of tourist revisit intention (Güçer and Arici, 2018; Preko et al , 2020a, b). Indeed, memorable and fascinating tour experiences are shared deliberately to promote future tourism behaviours and likelihood to revisit (Gannon et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, incorporation of artificial intelligence (AI) and robotics into the hospitality and tourism service sector (Kuo, 2009) seem unexploited (Tuominen and Ascencao, 2016), thus demanding that tour operators can take advantage of intelligent technology to remain sustainable and competitive in the mist of global tourism competition (Kuo, 2009). Preko et al (2020a, b) call upon tour practitioners to strategically imbibe smart technology to minimize possible service disruptions to prevent service failures that may negatively affect tourist loyalty.…”
Section: Introductionmentioning
confidence: 99%
“…This has made many countries tap into this niche by making diaspora tourism very attractive to those in the diaspora. In tourism extant literature, the issue of family and cultural heritage has long been argued as a community based resource (Hughes and Carlsen, 2010; MacDonald and Jolliffe, 2003; Preko et al , 2020a, c), and it is among the important factors that drive migrants to participate in diaspora tourism. However, family and cultural heritage predicting travel preference has gained little academic recognition.…”
Section: Introductionmentioning
confidence: 99%